Prehospital Emergency Care Training Practices Regarding Lesbian, Gay, Bisexual, and Transgender Patients in Maryland (USA). Issue 2 (27th February 2015) - Jalali, Sara; Levy, Matthew J.; Tang, Nelson
Abstract: Introduction: Prehospital Emergency Medical Services (EMS) providers are expected to treat all patients the same, regardless of race, gender identity, sexual orientation, or religion. Some EMS personnel who are poorly trained in working with lesbian, gay, bisexual, and transgender (LGBT) patients are at risk for managing such patients incompletely and possibly incorrectly. During emergency situations, such mistreatment has meant the difference between life and death. Methods: An anonymous survey was electronically distributed to EMS educational program directors in Maryland (USA). The survey asked participants if their program included training cultural sensitivity, and if so, by what modalities. Specific questions then focused on information about LGBT education, as well as related topics, that they, as program directors, would want included in an online training module. Results: A total of 20 programs met inclusion criteria for the study, and 16 (80%) of these programs completed the survey. All but one program (15, 94%) included cultural sensitivity training. One-third (6, 38%) of the programs reported already teaching LGBT-related issues specifically. Three-quarters of the programs that responded (12, 75%) were willing to include LGBT-related material into their curriculum. All programs (16, 100%) identified specific aspects of LGBT-related emergency health issues they would be interested in having included in an educational module. Conclusion: Most EMS educational program directors in Maryland are receptive to including LGBT-specific education into their curricula. The information gathered in this survey may help guide the development of a short, self-contained, open-access module for EMS educational programs. Further research, on a broader scale and with greater geographic sampling, is needed to assess the practices of EMS educators on a national level. S Jalali, MJ Levy, N Tang .Prehospital emergency care training practices regarding lesbian, gay, bisexual, and transgender patients in Maryland (USA) .Prehosp Disaster Med .2015 ;30 (2 ):1 -4 .